An actuator fault reconstruction scheme for linear systems. (August 2016) - Lee, Kee-Sang; Park, Tae-Geon
Highlights: This study has proposed an actuator fault reconstruction scheme for linear systems with applications to aircraft and crane models. The given system is decomposed into two subsystems; a fault-free subsystems and a fault-dependent subsystem. A functional observer is introduced to provide the estimate of the linear functions of the state of the fault-free subsystem. Robust exact differentiators are adopted to provide the derivative of the measurement output. Abstract: This paper presents an actuator fault reconstruction scheme that can be classified into an algebraic decomposition approach in which the original system is decomposed into two subsystems: a fault-free subsystem and a fault-dependent one. From the result of such algebraic decomposition, the fault estimate is obtained as a set of combinational functions of the system input, the measurement output, the estimate of certain linear functionals involving the state of the fault-free subsystem and the first-order derivative of the measurement output. Here a functional observer and robust exact differentiators are adopted to provide the estimate of the linear functionals of the state of the fault-free subsystem and the derivative of the measurement output, respectively. The proposed method is verified through two numerical examples of seventh-order aircraft and fourth-order crane models.